Finite-time attitude tracking control for rigid spacecraft with control input constraints - Zou, An-Min; de Ruiter, Anton H.J; Kumar, Krishna Dev (IET control theory & applications, 2017)
This study considers the problem of attitude tracking control for rigid spacecraft subject to control input saturation. To address this problem, a smooth model is first proposed to describe the input magnitude saturation. The output of the model is always in agreement with the constraints imposed by the actuators. Then, two finite-time attitude tracking control schemes are designed based on the model derived here and the homogeneous method. The measurement of angular velocity is required in the first scheme while it is relaxed in the second one. Finally, the effectiveness of the proposed control laws is illustrated by numerical simulations.